2017
DOI: 10.1103/physrevlett.119.032002
|View full text |Cite
|
Sign up to set email alerts
|

NRQCD Confronts LHCb Data on Quarkonium Production within Jets

Abstract: We analyze the recent LHCb measurement of the distribution of the fraction of the transverse momentum, z(J/ψ), carried by the J/ψ within a jet. LHCb data is compared to analytic calculations using the fragmenting jet function (FJF) formalism for studying J/ψ in jets. Logarithms in the FJFs are resummed using DGLAP evolution. We also convolve hard QCD partonic cross sections, showered with PYTHIA, with leading order Non-Relativistic Quantum Chromodynamics (NRQCD) fragmentation functions and obtain consistent re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 46 publications
5
52
0
1
Order By: Relevance
“…We found that this observable leads to even more discriminative power and it can, thus, provide better constraints for the LDMEs in global fits and more accurate information on the non-perturbative formation of heavy quarkonia. A complimentary study in [40] provided similar conclusions. We encourage the experimentalists to perform such measurements at the LHC and RHIC.…”
Section: Introductionsupporting
confidence: 70%
“…We found that this observable leads to even more discriminative power and it can, thus, provide better constraints for the LDMEs in global fits and more accurate information on the non-perturbative formation of heavy quarkonia. A complimentary study in [40] provided similar conclusions. We encourage the experimentalists to perform such measurements at the LHC and RHIC.…”
Section: Introductionsupporting
confidence: 70%
“…[32] (after this Letter was submitted, Ref. [59] demonstrated quantitative agreement). The lack of isolation observed for prompt J=ψ production may be related to the long-standing quarkonium polarization puzzle.…”
Section: H Y S I C a L R E V I E W L E T T E R S Week Ending 12 May 2017mentioning
confidence: 82%
“…In Ref. [15] for describing the production of quarkonium within jets in hadronic collisions we convolve the FJF with the corresponding hard scattering process evaluated using the monte-carlo software MadGraph [14],…”
Section: Review Of Fragmenting Jet Functionsmentioning
confidence: 99%
“…Particularly we propose a measurement of the quarkonium transverse momentum with respect to jet axis and we review the theoretical tools developed Figure 1: Predicted z(J/ψ) distribution using GFIP (gray) and FJF (red) for the three choices of LDME as described in the text and the LHCb measurements of z(J/ψ) [16]. Figure taken from [15] in Ref. [23] necessary for this calculation.…”
Section: Review Of Fragmenting Jet Functionsmentioning
confidence: 99%